NEMATODA PARASIT PADA TKUS DI DAERAH SEKITAR SELATSUNDA - ENDANG PURWANINGSIH; ACHMAD SAIM (Research Center for Biology-Indonesian Institute of Sciences, 1988)
E. PURWANINGSIH & A. SAIM. 1988.Nematode parasites infestation on rats in Sunda Strait and its vicinity.Berita Biologi 3(8): 386 - 389.Four species of parasitic nematode namely Cruzia sp.,Hepatojarakusmalayae,Molincus sp. andRictularia tani,were recovered from three species of rats.These rats were captured at Cidaun. Peucang Island and Rakata Island, located in the vicinity of Sunda Strait,West Java.Among the four species of nematode recovered, Cruzia sp.had never been reported infesting rats before.